Wind-induced failure analysis of a transmission tower-line system with long-term measured data and orientation effect. (January 2023) - Bi, Wenzhe; Tian, Li; Li, Chao; Ma, Zhen; Pan, Haiyang
Highlights: Measured wind data in 50 years is collected for performance analysis of a TTLS. JPD of wind speed and direction is developed using a QS copula-based model. Failure analyses considering structural safety and serviceability are performed. A novel framework is presented to compute the actual failure probability and identify the optimal orientation of TTLSs. Abstract: This paper proposes a comprehensive wind-induced performance evaluation framework for transmission tower-line systems (TTLSs) from both structural safety and normal operation dimensions, incorporating the joint effect of wind speed and direction, as well as the line orientation. Based on the field wind data recorded in Weifang, China during 1971–2020, the actual failure probability of a local TTLS is calculated considering the joint probability distribution (JPD) of wind speed and direction, and the optimal layout of the transmission line is provided. The results show that the developed QS copula model can not only account for the continuity and cyclicity of wind direction but also have a fine goodness-of-fit. The wind direction with a relatively lower occurrence probability does not necessarily yield smaller failure probability of the TTLS, thereby the JPD of wind speed and direction should be incorporated to achieve reliable performance assessment. For the failure analysis with respect to structural damage, the most favorable layout of the exemplar TTLS is the orientation of 265°; while the most advantageous layout is the orientation of 38° in terms of flashover risk. The presented framework is conducive to performance assessment and optimization design of TTLSs subjected to wind hazards.